Understanding Maternal Health with special signicance to Antenatal Care: A Micro Level Study of Village Khagawal, District Chandauli, Uttar Pradesh - Singh, Divyanshi (National Geographical Journal of India, 2022)
Women's right to have choices, sense of self- worth and their right to have access to opportunities have been a subject of serious concern. The level of human development in the society is reection of better status of a woman, which has a clear impact on the usage of contraceptive methods and maternal health. The study is an attempt to assess the performance of Uttar Pradesh on the parameters of levels of human development and to see how the developmental trajectory is inuencing the choice for contraception and maternal health. Multiple Regression has been done to analyse the relationship between development aspect, contraception and maternal health. Better education and health facilities along with good income show strong impact on choice of contraception which ultimately leads to better maternal health